Analisis Pengaruh Risiko Kredit, Risiko Likuiditas, serta Risiko Operasional Terhadap Kinerja Perbankan: Studi Kasus pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Yunike, Jihan; Gandakusuma, Imo (UI Scholars Hub, 2023)
Researchers conducted research on banks in Indonesia to assess the effect of credit risk, liquidity risk, and operational risk on banking financial performance. Data is obtained from the IDX website and banks from 38 conventional commercial banks that met the criteria for the 2016-2020 period. Researchers used the fixed-effect model (FEM) to analyze the results of this study.The results of this study indicate that credit and operational risks have a significant effect on the company's financial performance. On the other hand, liquidity risk has an insignificant effect on the company's financial performance. The results can be used by the company's management team as a reference in making decisions related to risk management, especially credit risk, liquidity risk, and operational risk in banking. After studying this research, it is hoped that the management team will have an overview of the effects of these risks on banking financial performance. Credit, liquidity and operational risks are considered the most important risks in financial institutions. This research is the second research that examines the effect of these risks on the banking industry; however, this research focuses on banks in Indonesia.